2003
DOI: 10.1109/mcom.2003.1193973
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and evaluation of the indoor power line transmission medium

Abstract: The aim of this articlc is to outline the possibilities of indoor power lines when used to supp o r t local area networks in homes o r small offices. For this purpose, the channel characteristics are described and a channel model is presented. This model is related to the physical nature of common indoor power lines, so its parameters can be defined in a straightforward way. Bascd on it, performance of communication systems that use discrete multitone modulation, which appears to he the most suitable technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 4 publications
0
46
0
1
Order By: Relevance
“…Once the devices have been modeled as loads associated to a certain outlet, the transmission and reception points completely determine the channel response. Even more, if devices behavior is known, it is possible to generate feasible PLC channels from actual devices measurements and a good characterization of the wiring [3].…”
Section: Indoor Power Network Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Once the devices have been modeled as loads associated to a certain outlet, the transmission and reception points completely determine the channel response. Even more, if devices behavior is known, it is possible to generate feasible PLC channels from actual devices measurements and a good characterization of the wiring [3].…”
Section: Indoor Power Network Structurementioning
confidence: 99%
“…The main goal of this paper is the characterization of the high-frequency properties of indoor power lines, putting emphasis on their short-time variation. Thus, this work tries to complement previous ones that analyze channel performance obviating this aspect [2], [3], [5]- [7]. This paper is organized as follows.…”
Section: Introductionmentioning
confidence: 99%
“…According to this, Table 1 shows approximate values of the optimum cyclic prefix lengths. It can also be observed that the most appropriate number of carriers is N = 2 13 , although the averaged bit-rate loss is still below 3.5% for N = 2 12 . In a 25 MHz frequency band, N = 2 13 results in a carrier bandwidth of 3.1 kHz.…”
Section: Selection Of the Modulation Parametersmentioning
confidence: 96%
“…Hence, enlarging the cyclic prefix improves the data rate only if the power of the remaining distortion due to the frequency selectivity stays much greater than the noise and the distortion caused by the channel time variation. Once the contribution of the latter terms dominates, lengthening the cyclic prefix is counterproductive because the OFDM symbol rate is reduced without profit [12]. Therefore, there exist optimum values for both the number of carriers and the cyclic prefix length.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the measurements, published in [9] and [17], show the value of characteristic impedance 80 -90 Ω, which corresponded with our model. On the other hand, in [18] the value 200 Ω was introduced for characteristic impedance, which corresponded with the FTW PLC model.…”
Section: Comparison Of the Calculations Of Primary Parametersmentioning
confidence: 99%